EFFECT OF COOKING METHODS ON THE REDUCTION OF LEAD (Pb) CONTENT IN KEPAH (Polymesoda erosa) SHELLS - Warsidah Warsidah; Mega Sari Juane Sofiana; Agus Yuliono; Lucky Hartanti; Dwi Gusmalawati; Ikha Safitri; Risko Risko; Jannati Jannati (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2022)
Kepah shells have important economic value and are widely used as food ingredients because they contain high nutritional content. Heavy metals that enter the waters will generally be accumulated in sediments and absorbed by biota. As filter feeder, Kepah accumulate heavy metals from the environment that toxic to humans. This study aimed to determine the effect of cooking methods on the concentration of lead (Pb) in Kepah shell. The measurement of Pb content was conducted according to SNI 2345.5-2011 by Atomic Absorption Spectrophotometer (AAS). Result showed that different cooking methods influenced the Pb content in Kepah shells. Frying and boiling processes reduced the Pb concentration of 46.34% and 31.48%, respectively. According to the result, frying suggested as the best cooking method to provide healthful food for consumption.